Embolization of Large and Giant Posterior Fossa Hemangioblastomas: The Experience of a Single Tertiary Care Center - Bauman, Megan M.J.; Bouchal, Samantha M.; Kerezoudis, Panagiotis; Cloft, Harry; Brinjikji, Waleed; Peris Celda, Maria; Link, Michael J.; Parney, Ian F. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Background Hemangioblastomas pose an inherent surgical risk due to the potential for high intraoperative blood loss, especially in larger tumors. One approach to minimize this risk is to use preoperative embolization. Herein, we present our institutional experience treating large and giant cerebellar hemangioblastomas.Methods We performed a retrospective chart review of 19 patients with cerebellar hemangioblastomas that had a maximal diameter of >3 cm. We performed a literature review and included individual patient-level data that met our >3 cm diameter cerebellar hemangioblastoma inclusion criteria.Results Our cohort consisted of 19 patients that received a total of 20 resections for their cerebellar hemangioblastomas. Preoperative embolization was utilized in eight cases (38.1%). One patient experienced transient neurological complications after embolization (12.5%). Tumors of patients in the embolization group had larger median total, solid, and cystic volumes and were more likely to involve the cerebellopontine angle than those in the non-embolized group. Compared with non-embolized patients, embolized patients had less decrease in their hemoglobin, lower volumes of estimated blood loss, reduced rates of postoperative complications and permanent deficits, and greater instances of neurological improvement. The larger cohort (obtained from the combining our cohort with patients identified during a literature review) consisted of 99 patients with 39 receiving preoperative embolization.Conclusion It is important to examine individual patient characteristics when determining eligibility for preoperative embolization. However, improvements in endovascular techniques have made preoperative embolization a safe and effective procedure with minimal risks that can be performed in many patients.
Keywords: cerebellar; hemangioblastoma; embolization; surgical outcomes; posterior fossa